2015
DOI: 10.1080/15548627.2015.1106662
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy of metallothioneins prevents TNF-induced oxidative stress and toxicity in hepatoma cells

Abstract: , tandem fluorescent microtubule-associated protein 1 light chain 3 A/B (green/red fluorescent proteins chimera); TNFRSF1A/TNFR1, tumor necrosis factor receptor superfamily member 1A; TNFRSF1B/TNFR2, tumor necrosis factor receptor superfamily member 1B.Lysosomal membrane permeabilization (LMP) induced by oxidative stress has recently emerged as a prominent mechanism behind TNF cytotoxicity. This pathway relies on diffusion of hydrogen peroxide into lysosomes containing redox-active iron, accumulated by breakdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 67 publications
4
34
0
Order By: Relevance
“…Autophagy has long been recognized as an important intracellular process used to degrade cellular contents through lysosomes [31]. Previous studies have demonstrated that autophagy has an intimate connection with immunity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy has long been recognized as an important intracellular process used to degrade cellular contents through lysosomes [31]. Previous studies have demonstrated that autophagy has an intimate connection with immunity [32].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas OS impairs autophagy, MT helps maintain it. Lysosomal delivery of MT protects cells against apoptosis by modulation of autophagy . Metallothionein has been reported to inhibit biological membrane lipid peroxidation injury and to improve recovery after transient myocardial ischemia–reperfusion‐induced injuries …”
Section: Metallothionein and Its Broad‐spectrum Functionsmentioning
confidence: 99%
“…Lysosomal delivery of MT protects cells against apoptosis by modulation of autophagy. 145 Metallothionein has been reported to inhibit biological membrane lipid peroxidation injury and to improve recovery after transient myocardial ischemia-reperfusion-induced injuries. 146 Extracellular MT and anti-inflammatory and immune function Extracellular MTs have been confirmed and their functions are gradually being determined, [31][32][33][37][38][39][40] including immune regulation 36 and neuronal protection.…”
Section: Induction Of Lysosomal Membrane Permeabilizationmentioning
confidence: 99%
“…In humans, MTs are encoded by 17 genes, with four defined subtypes (MT1‐MT4). MTs are increased during oxidative stress states in order to protect cells against cytotoxicity, radiation, and DNA damage . MT1 family (MT1s) is comprised of eight functional members: MT1A, MT1B, MT1E‐H, MT1M, and MT1X …”
Section: Introductionmentioning
confidence: 99%
“…MT1s are involved in diverse functions, such as metal homeostasis, metal donation to different enzymes, angiogenesis, apoptosis, cell differentiation, radiation cell damage as well as carcinogenesis . Given their broad regulatory properties, MT1s have also been suggested to play important roles in cell senescence and various pathological processes, such as neurodegeneration, osteoarthritis, metabolic disorders, and certain immune processes .…”
Section: Introductionmentioning
confidence: 99%